Meta Analisis Pengaruh Pola Asuh Dalam Memberikan Gadget Terhadap Sosial Emosional Anak Usia Dini - Aisyah Amalia Khoirul Amini; Nailul Azizah; Siti Salwa; Fidrayani Fidrayani (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to compare several aspects of research results between 2019 and 2024. The method used is preferred reporting items for systematic reviews and meta analyzes (PRISMA). This article discusses the influence of parenting styles in providing gadgets on the social emotional development of early childhood. The results of this research also show that the way parents allow their children to use gadgets greatly influences their social and emotional development. The size of its influence is very significant for children. Around 9.5% to 14.2% of children experience social and emotional problems in the age range of zero to five years, which can affect their developmental abilities and readiness to enter school.